Pharmacokinetics and Absolute Bioavailability of Oral Foscarnet in Human Immunodeficiency Virus-Seropositive Patients - Noormohamed, Faruq H. (American Society for Microbiology, 1998)
The pharmacokinetics, absolute bioavailability, accumulation, and tolerability over 8 days of an oral formulation of foscarnet (90 mg/kg of body weight once daily [QD] [n = 6], 90 mg/kg twice daily [BID] [n = 6], and 180 mg/kg QD [n = 3]) were investigated in 15 asymptomatic, human immunodeficiency virus-seropositive male patients free of active cytomegalovirus infection and with normal upper gastrointestinal function. Peak plasma drug concentrations were (mean ± standard deviation) 46.4 ± 10.8 μM (90 mg/kg QD), 45.7 ± 6.9 μM (90 mg/kg BID), and 64.9 ± 31.7 μM (180 mg/kg QD) on day 1 and rose to 86.2 ± 35.8, 78.7 ± 35.2, and 86.4 ± 25.0 μM, respectively, on day 8. The mean peak concentration in plasma following the intravenous administration of foscarnet (90 mg/kg) was 887.3 ± 102.7 μM (n = 13). The terminal half-life in plasma remained unchanged, averaging 5.5 ± 2.2 h on day 1 (n = 15) and 6.6 ± 1.9 h on day 8 (n = 13), whereas it was 5.7 ± 0.7 h following intravenous dosing. Oral bioavailabilities were 9.1% ± 2.2% (90 mg/kg QD), 9.5% ± 1.7% (90 mg/kg BID), and 7.6% ± 3.7% (180 mg/kg QD); the accumulation ratios on the 8th day of dosing were 2.1 ± 1.1, 1.8 ± 0.4, and 1.7 ± 0.7, respectively. The overall 24-h urinary excretion of oral foscarnet averaged 7.8% ± 2.6% (day 1) and 13.4% ± 6.0% (day 8), whereas it was 95.0% ± 4.9% after intravenous dosing. The glomerular filtration rate and creatinine clearance remained constant, and the mean 24-h renal clearances of foscarnet for the entire study group were 96 ± 18 ml/min (day 1), 88 ± 13 ml/min (day 8), and 103 ± 16 ml/min after intravenous dosing. Adverse effects were largely confined to gastrointestinal disturbances, with all subjects experiencing diarrhea that was dose dependent in its severity. The results suggest that the formulation studied would require significant improvement with respect to tolerability and bioavailability to gain clinical acceptance.